Quantifying tsunami impact on industrial facilities and production capacity in ports: An application to Sendai Port, Japan. (August 2022) - Suppasri, Anawat; Nishida, Tomoki; Pakoksung, Kwanchai; Cheng, An-Chi; Chua, Constance Ting; Iwasaki, Tomoya; Pescaroli, Gianluca; Imamura, Fumihiko
Abstract: The 2011 Great East Japan earthquake and subsequent tsunami is one of the costliest natural hazards to date. Losses were not only from physical damage alone. Indirect losses due to business interruptions and their consequential impacts on the rest of the economy and supply chain account for most losses. In this study, 12 companies across five industrial sectors in Miyagi Prefecture were interviewed to gain a better understanding about the damage that were sustained by their factories during the 2011 Great East Japan earthquake and tsunami as well as subsequent earthquake and tsunami events. The study investigates (i) the vulnerability of mechanical structures to tsunami impacts, and (ii) the recovery rates of production capacity for various industrial sectors through interviews with companies from various industrial sectors. In addition, tsunami risk assessment is performed for future tsunami scenarios using Sendai Port as a case study. Results from this study indicate that only 1–2 m of flow depth is enough to cause damage to mechanical structures in most industries, which disrupts operations. In addition, recovery rates of production capacity vary at different tsunami inundation levels. Full recovery of production capacity can occur as quickly as 1–2 months later and as late as 10–12 months later depending on the situation. Tsunami risk assessment demonstrates that using structural fragility functions alone might underestimate the actual loss of industries and that most industries in Sendai Port are potentially capable of recovering within eight months after large future tsunami.